2019
DOI: 10.3390/w11030512
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Influence of Hydrological Regime on Organic Matters Characteristic in a Korean Watershed

Abstract: Source tracking of dissolved organic matter (DOM) is important to manage water quality in rivers. However, it is difficult to find the source of this DOM because various DOMs can be added from the river watershed. Moreover, the DOM composition can be changed due to environmental conditions. This study investigated the change of organic matter characteristics in the Taewha River of Ulsan City, Korea, before and after rainfall. A Soil and Water Assessment Tool (SWAT) was used to simulate water flow from various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The compositional differences and the characteristics of marine DOM are still largely unidentified because the very low concentrations of DOM in seawater, compared to the massive amounts of inorganic sea salts, present a major challenge (Hansell and Carlson, 2002;Park S. et al, 2019). Recently, high-resolution mass spectrometry (HRMS) has been applied to identify the molecular signatures of DOM (Koch et al, 2008;Phungsai et al, 2016;Baek et al, 2019). HRMS has far higher sensitivity and resolving power in identifying mass spectral peaks than the existing mass spectrometry (MS) methods (Koch et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The compositional differences and the characteristics of marine DOM are still largely unidentified because the very low concentrations of DOM in seawater, compared to the massive amounts of inorganic sea salts, present a major challenge (Hansell and Carlson, 2002;Park S. et al, 2019). Recently, high-resolution mass spectrometry (HRMS) has been applied to identify the molecular signatures of DOM (Koch et al, 2008;Phungsai et al, 2016;Baek et al, 2019). HRMS has far higher sensitivity and resolving power in identifying mass spectral peaks than the existing mass spectrometry (MS) methods (Koch et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the pristine nature of the basin, this also may have measurable yet unknown consequences for the export of DOC and nutrients from soils to rivers, and ultimately for the fjord. Although most studies focus on temperate, boreal and artic regions, it is well known that changes in hydrological regimes influence the export of DOC in relatively undisturbed basins (Winterdahl et al, 2016;Baek et al, 2019;Connolly et al, 2020). Unfortunately, our shortterm study in terms of water chemistry cannot illuminate this issue, and there are no long-term records of organic matter and nutrient export from Patagonian basins to support claims related to changes in hydrological regimes.…”
Section: Figure 8 | (A)mentioning
confidence: 84%
“…The understanding of water quality or biologic processes should be based on source locality and pathway conditions. Baek et al 2019 [14] used an effective approach to find sources of DOM (dissolved organic matter) in rivers by coupling the SWAT (Soil and Water Assessment Tool) model with organic matter characterization and concluded that lateral flow transported hydrophobic and large-molecule organic matter after rainfall.…”
Section: Summary Of This Special Issuementioning
confidence: 99%